Chord failure resistance of 3D cut welded connections with CHS columns and through I-BEAMS. (September 2020) - Di Benedetto, S.; Latour, M.; Rizzano, G.
Abstract: This paper deals with the study of the mechanical behaviour of a novel typology of steel beam-to-column connection made by welding circular hollow section (CHS) columns with through-all I-beams. Such connection represents an alternative to the classical configuration with the I-beam simply welded to the external surface of the hollow profile for which Eurocode 3 part 1.8 provides specific design rules resulting from the "ring model" theory. The main features of connections with through-all beams derive from a change of the resisting mechanism which leads to a significant increase of stiffness and resistance. Nevertheless, such a change of the mechanical behaviour, strictly affected by the different plasticity pattern, is not considered in the classical ring model theory. Within this framework, in this paper the flexural resistance of connections with CHS columns and through-all I-beams is assessed by developing experimental tests and analytical models aiming to propose a new design equation. Specifically, two cyclic ad two monotonic tests on real scale beam-to-column connections have been executed at the laboratory of the University of Salerno. Subsequently, finite element (FE) models have been calibrated and verified against the experimental results. Then, the developed FE models have been extended to perform parametric analyses to be used to verify the accuracy of a new theoretical approach able to predict the plastic resistance of such a kind of connections. The theoretical approach has been developed basing on the plasticity theory and exploiting the previous knowledge based on the so-called ring model. The proposed formulations, when compared to the available experimental data and FE simulations, have proved to exhibit a high accuracy. Highlights: Experimental tests on beam-to-column joints with through-all beam are presented. The performance of connections with through-all beam is compared to the performance of connections externally welded. A FE model of the connection is built and exploited to perform parametric studies. Two alternative design equations able to predict the resistance of the connection are developed. The accuracy of the equations is verified against FE data showing a high accuracy.